2019
DOI: 10.1055/s-0039-1698810
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety and Efficacy Data of a Plasma-Derived Factor VIII Concentrate with von Willebrand Factor for Treatment of Patients with Hemophilia A Covering 18 Years

Abstract: We describe the results of the (to our knowledge) longest long-term noninterventional study so far performed to obtain real-life data on the treatment of hemophilia A patients with a single plasma-derived FVIII concentrate containing von Willebrand factor (pdFVIII; Haemoctin/Faktor VIII SDH Intersero). A total of 198 patients (146 in Germany and 52 in Hungary), of whom 160 had severe and 38 nonsevere hemophilia A, representing all age groups (0–88 years; mean ∼25 years at inclusion) were analyzed during prophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 39 publications
2
8
0
Order By: Relevance
“…Therefore, these data cannot be compared directly with treatment data from (randomized) clinical trials. 32 However, median ABR under continuous prophylaxis in the present study (1.3) was comparable with that observed in clinical trials with other FVIII products (median 0.0-2.0) with observation periods of about 6 months. 20,[27][28][29]40…”
Section: Ta B L E 2 (Continued)supporting
confidence: 87%
See 4 more Smart Citations
“…Therefore, these data cannot be compared directly with treatment data from (randomized) clinical trials. 32 However, median ABR under continuous prophylaxis in the present study (1.3) was comparable with that observed in clinical trials with other FVIII products (median 0.0-2.0) with observation periods of about 6 months. 20,[27][28][29]40…”
Section: Ta B L E 2 (Continued)supporting
confidence: 87%
“…9,[13][14][15][16][17][18][19][20][21][22][23][24][25][26]34 This prospective study is the longest NIS of a single FVIII concentrate reported so far in which treatment data were collected from the routine treatment of HA patients. 32 In a broad range of patients with severe as well as non-severe HA, covering all age groups up to 88 years, long-term prophylaxis with a pdFVIII concentrate reduced the ABR remarkably, in some cases down to zero.…”
Section: Ta B L E 2 (Continued)mentioning
confidence: 99%
See 3 more Smart Citations